Developing a Teacher Module on the Application of Unplugged Coding in Handwashing Skills Learning for Children with Down Syndrome - Wulandari Eni; Chamidah Atien Nur (Jurnal Teknologi Informasi dan Pendidikan, 2026)
This study aims to develop a teacher module on the application of unplugged coding (coding without a computer) in learning handwashing skills for children with Down syndrome. This study also aims to test the feasibility of the module based on the assessment of material experts and media experts, as well as to test the Pub. effectiveness of the module in improving teacher competency. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) The resulting product is a Google Sites-based digital module called “SI TEPAT”. The validation results show that this module is "Very Feasible" with a score of 97.3% from material experts and 93% from media experts. The effectiveness test on 105 SLB teachers showed a significant increase in pre-test and post-test results, proving that this module is effective in improving teacher understanding in teaching coding concepts through daily activities.